1978
DOI: 10.2307/2937299
|View full text |Cite
|
Sign up to set email alerts
|

Factors Regulating the Distribution and Population Dynamics of the Amphipod Gammarus palustris in an Intertidal Salt Marsh Community

Abstract: Seasonal changes in the intertidal distribution, abundance and population dynamics of the epifaunal amphipod Gammarus palustris were studied in salt marshes bordering 2 estuarine rivers flowing into the Chesapeake Bay. The amphipod populations inhabiting the Patuxent River study site showed abundance peaks during the spring and autumn, and major declines in density during the summer and winter. Populations at 2 study sites in the Rhode River showed only 1 peak of abundance during the late spring and early summ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
66
0
1

Year Published

1988
1988
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(74 citation statements)
references
References 38 publications
7
66
0
1
Order By: Relevance
“…These amphipods are morphologically very similar, and like most free-living vegetation-dwelling amphipods, are highly thigmotactic (Nagle 1968, van Dolah 1978. Preliminary observations indicated that both preferred to occupy spaces between basal portions of grassblades, demonstrated comparable activities and movements, and interacted with pipefish in identical manners.…”
Section: Methodsmentioning
confidence: 85%
See 2 more Smart Citations
“…These amphipods are morphologically very similar, and like most free-living vegetation-dwelling amphipods, are highly thigmotactic (Nagle 1968, van Dolah 1978. Preliminary observations indicated that both preferred to occupy spaces between basal portions of grassblades, demonstrated comparable activities and movements, and interacted with pipefish in identical manners.…”
Section: Methodsmentioning
confidence: 85%
“…Two Gammarus spp, were used interchangeably as prey: G. mueronatus, an inhabitant of eelgrass and algal communities (Fredette & Diaz 1986), and G. palustris, an intertidal marsh inhabitant (van Dolah 1978). These amphipods are morphologically very similar, and like most free-living vegetation-dwelling amphipods, are highly thigmotactic (Nagle 1968, van Dolah 1978.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since Gammarus individuals compete for the refuge that substratum provides, their average size is usually higher in the benthos than in the water column (Van Dolah 1978, Newman & Waters 1984, Morillo-Velarde et al 2011. On the assumption that this pattern is similar in G. aequicauda, the increase of the G. aequicauda biomass consumed by the toothcarp and the diminution of such consumption in the mosquitofish could reflect a shift in feeding strategy with reduced salinity.…”
Section: Discussionmentioning
confidence: 97%
“…Estuarine epibenthic amphipods are typically found on a wide range of substrates (Levings eta!., 1975;Van Dolah, 1978;Borowsky et a!., 1985). Eogammarus confervicolus is no exception and throughout brackish waters of the north-east Pacific, can routinely be found under various species of algae, marsh plants, wood debris and rocks (Pomeroy & Levings, 1980;Stanhope & Levings, 1985).…”
Section: Introductionmentioning
confidence: 99%